The Model of Master’s Degree Program in Product Design Engineering - Vladimir D. Nechaev; Maxim P. Evstigneev; Veronika R. Dushko (Высшее образование в России)
The paper presents the model of Master’s Degree Program in Product Design Engineering implemented for training engineers majoring in “Innovation shipbuilding”. The program is being rolled out as a pilot project since 2017 on the basis of the Institute of National Technological Initiative of Sevastopol State University. The ideology of Master’s programs in Product Design Engineering generally matches with the paradigm of context education, nevertheless it has its own specific features, such as the principle of diploma project readiness (as a product of Master’s program) to enter into the market, and the evaluation of the product by expert community; training of the graduates to professional activity as ‘chief designer managers’, who understand the principles of how to organize the team of specialists and to obtain the required result as a market product; simulation by the students of the role of a customer for the object of designing, and preparation of the future engineer taking into account not only object designing, but also future utilization, that is, the whole life cycle. Special attention is paid to so called “distributed design”, which enables to organize a virtual professional environment of a “design bureau” bringing together different student project groups.